Pelatihan Pemanfaatan Likat Biru untuk Pengendalian Thrips pada Pepaya di Kelompok Tani Mulyo, Bandongan, Magelang - Fitrianoor Setyaningsih; Yovi Avianto; Muhammad Izzul Farkhi; Muhammad Parikesit Wisnubroto (Buletin Dharmas Andalas, 2026)
Thrips are among the important pests in papaya cultivation because they damage young leaves and flowers and may reduce plant vigor and fruit set. Community service was conducted for members of Kelompok Tani Mulyo in Bandongan, Magelang, to improve farmers’ knowledge and skills in using blue sticky traps as a simple, low-cost, and environmentally safer component of integrated pest management. The activities consisted of field observation, counseling, demonstration, guided installation of traps, and evaluation through discussion and pretest–posttest instruments. The material covered thrips identification, the principles of blue color attraction, trap installation techniques, field sanitation, and routine monitoring. The activity was designed to strengthen farmers’ capacity to detect pest presence earlier and to reduce dependence on repeated insecticide applications. Qualitatively, the program increased participants’ understanding of thrips symptoms, trap placement, monitoring schedules, and the role of non-chemical control in papaya cultivation. The main outcome was the adoption of a practical monitoring and suppression tool that can be directly implemented at farm level. This service activity shows that blue sticky trap training is relevant, feasible, and potentially scalable for farmer groups facing thrips problems in papaya fields